Management of Jugular Bulb Injuries during Endoscopic Ear Surgery: Our Experience - Ferri, Gaetano; Fermi, Matteo; Alicandri-Ciufelli, Matteo; Villari, Domenico; Presutti, Livio (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives The main objective of this article is to describe endoscopic management of intraoperative massive bleeding from jugular bulb injury during exclusively transcanal endoscopic procedures for middle ear pathologies.Design Case series with chart review.Setting Tertiary referral center.Participants We retrospectively reviewed two patients who experienced jugular bulb injury during endoscopic transcanal approach for glomus tympanicum and chronic otitis media. The surgical videos and charts were carefully investigated and analyzed.Main Outcome Measures Feasibility and suitability of exclusive endoscopic management of jugular bulb bleeding and description of surgical maneuvers that should be performed to obtain safe and effective hemostasis.Results In both patients, jugular bulb bleeding was progressively controlled by means of exclusive endoscopic approach with no need to convert to microscopic approach. None of the cases required a second surgeon helping in keeping the endoscope during hemostatic maneuvers. Both patients had a normal postoperative period with no recurrence of hemorrhage.Conclusions Endoscopic management of jugular bulb bleeding is feasible by using the technique described with reasonable efficacy and with no additional risk or morbidity to the procedure. Knowledge of anatomy and its variants, preoperative evaluation of imaging, and the ability of the surgeon to adapt the surgical technique to the specific case are recommended to prevent vascular complications during endoscopic ear surgery.
Keywords: endoscopic ear surgery; bleeding management; jugular bulb dehiscence; high-positioned JB